Host chitinase 3-like-1 is a universal therapeutic target for SARS-CoV-2 viral variants in COVID-19 - Suchitra Kamle; Bing Ma; Chang Min Lee; Gail Schor; Yang Zhou; Chun Geun Lee; Jack A Elias (eLife, 2022)
Coronavirus disease 2019 (COVID-19) is the disease caused by severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2; SC2), which has caused a worldwide pandemic with striking morbidity and mortality. Evaluation of SC2 strains demonstrated impressive genetic variability, and many of these viral variants are now defined as variants of concern (VOC) that cause enhanced transmissibility, decreased susceptibility to antibody neutralization or therapeutics, and/or the ability to induce severe disease. Currently, the delta (δ) and omicron (ο) variants are particularly problematic based on their impressive and unprecedented transmissibility and ability to cause breakthrough infections. The delta variant also accumulates at high concentrations in host tissues and has caused waves of lethal disease. Because studies from our laboratory have demonstrated that chitinase 3-like-1 (CHI3L1) stimulates ACE2 and Spike (S) priming proteases that mediate SC2 infection, studies were undertaken to determine if interventions that target CHI3L1 are effective inhibitors of SC2 viral variant infection. Here, we demonstrate that CHI3L1 augments epithelial cell infection by pseudoviruses that express the alpha, beta, gamma, delta, or omicron S proteins and that the CHI3L1 inhibitors anti-CHI3L1 and kasugamycin inhibit epithelial cell infection by these VOC pseudovirus moieties. Thus, CHI3L1 is a universal, VOC-independent therapeutic target in COVID-19.